Effective operational control in scheduled waste reduction in manufacturing sector by implement ISO 14001 / Nik Asma' Nik Mohd Yusoff - Nik Mohd Yusoff, Nik Asma' (2009)
Improving the environmental performance of industry is one way of eliminate environmental problems. Nowadays, our industrial structure and consumption pattern are not friendly. Environmental management systems (EMS), such as ISO 14001, provide framework for organization wishing to manage the organization in an environmentally friendly mode. Implementing an EMS that conforms to the ISO 14001 standard may help organization to deal with global environmental regulations. This research helps bridge the gap between EMS theory and operations practices. It goals were to know the operation control in scheduled waste reduction in effectively that protects the environment. This goals were fulfilled through a case study of Panasonic Air- Conditioning Factory. The production of waste throughout Malaysia and the rest of the world is increasing at a rapid pace. As countries become more industrialized and the wealth of the citizens increases, there is an increase demand for goods and services. Corporation looking to increase sales and therefore profits often feed this craving with advertising for their products. The results is an ever-spiraling demand for goods resulting in more and more wastes (Goh, Kiam Seng, 1990, Kreith, F, 1994 and Bishop, P. L 2000). The environmental impacts of this have been all too evident: despoiled air and water, hazardous waste dumps, rapidly depleted resources and other environmental problems.